Answer:
x = 4.2 and -1.2
Step-by-step explanation:
Given the following function
f(x) = x^2 + 13
g(x) = 3x+18
If f(x) = g(x) then;
x^2 + 13 = 3x + 18
x^2 - 3x + 13 - 18 = 0
x^2 - 3x - 5 = 0
Factorize and find x
a = 1, b = -3 and c = -5
![\begin{gathered} x\text{ = }\frac{-(-3)\pm\sqrt[\square]{(-3)^2-4(1)(-5)}}{2} \\ x\text{ = }\frac{3\pm\sqrt[\square]{9+20}}{2} \\ x\text{ =}\frac{3\pm\sqrt[\square]{29}}{2} \\ x\text{ =}(3+5.38)/(2)\text{ or }(3-5.38)/(2) \\ x\text{ = 8.38/2 }or\text{ }-(2.38)/(2) \\ x\text{ = }4.19\text{ or }-1.19 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8lsz93y8a209kj0u6nsm5jgeqeegceqg7q.png)
To the nearest tenth, x = 4.2 and -1.2